Principles of molecular virology - Cann, Alan (Elsevier Academic Press, 2005)
Principles of Molecular Virology, Fourth Edition provides an essential introduction to modern virology in a clear and concise manner. It is a highly enjoyable and readable text with numerous illustrations that enhance the reader's understanding of important principles.